2012
DOI: 10.1055/s-0032-1306266
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Combination of the Dopamine and Serotonin Scaffolds Yield in Novel Antipsychotic Drug Candidates - Characterization by in vivo Experiments

Abstract: Serotonin and dopamine play an important role in the aetiology of schizophrenia. Combination of the structural scaffolds of both neurotransmitters in a single molecule lead to aromatic [d,g]-bisannelated azecine derivatives, which have been shown to be nanomolar to subnanomolar dopamine D1-D5 receptor antagonists with a preference for the D1 family. In this work the potential antipsychotic activity of some azecine derivatives was predicted by their dopamine receptor affinities obtained in vitro from radioligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Due to their phenolic nature, these compounds are predisposed to poor pharmacokinetics (low bioavailability), which would restrict their utility for in vivo experiments and render them unsuitable for clinical development. Accordingly, our preliminary in vivo evaluations have shown that compound 1 (LE404) has a low oral bioavailability when administered to rats [6]. Studies on other classes of phenolic dopamine antagonists, in particular SCH23390 and SCH39166, have led to similar results [7] [8].…”
mentioning
confidence: 79%
“…Due to their phenolic nature, these compounds are predisposed to poor pharmacokinetics (low bioavailability), which would restrict their utility for in vivo experiments and render them unsuitable for clinical development. Accordingly, our preliminary in vivo evaluations have shown that compound 1 (LE404) has a low oral bioavailability when administered to rats [6]. Studies on other classes of phenolic dopamine antagonists, in particular SCH23390 and SCH39166, have led to similar results [7] [8].…”
mentioning
confidence: 79%
“…Thus, azecines are a novel class of antidopaminergic drug candidates with preferential binding to the D 1 receptor subtype (D 1 ,D 5 ) [5]. Moreover, tests have shown that they bind as antagonists at the 5-HT 2A receptor [11]. Up to now no D 5selective drugs are available and the function of the D 5 -receptor is not yet understood exactly [1].…”
Section: Synthesis and Characterization Of New Azecine-derivatives Asmentioning
confidence: 99%
“…For receptor functionality, the substitution pattern is fundamental [11]. Various derivatives (▶Fig.…”
Section: Synthesis and Characterization Of New Azecine-derivatives Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, it may be possible to design new drugs with combinations of affinities that avoid those known to be associated with side-effects. For instance, the combination of the 'structural scaffolds' of dopamine and serotonin has produced a group of azecine derivatives, which are effective in animal models of psychosis but manifest substantially better tolerability than both haloperidol and risperidone [20].…”
Section: Future Prospects and Challenges Dopamine Receptor Antagonistsmentioning
confidence: 99%